Coffee Joy Cafe's customer service communication strategy to attract customers (Literasi Nusantara, 2025)
This study aims to analyze the communication strategies implemented by customer service at Café Kopi Joy in attracting customers, particularly in the campus environment. This research employs a qualitative descriptive approach using a constructivist paradigm. Data were collected through in-depth interviews, observation, and documentation involving the café owner, manager, customer service staff, and customers. The findings indicate that customer service communication strategies prioritize interpersonal relationships rather than direct promotional efforts. The application of FIRO theory covering inclusion, control, and affection is reflected in friendly greetings, clear service explanations, and warm, empathetic interactions with customers. These strategies contribute to customer comfort, positive service experiences, and increased interest in revisiting the café. This study highlights the importance of customer service communication as a strategic element in attracting customers in a competitive café industry.
Keywords: Communication Strategy; Customer Service; Café; Customer Attraction